2019
DOI: 10.24136/eq.2019.025
|View full text |Cite
|
Sign up to set email alerts
|

Do SME?s innovation strategies influence their effectiveness of innovation? Some evidence from the case of Podkarpackie as peripheral region in Poland

Abstract: Research background: Innovation is a very important pillar within a knowledge-based economy, in the regional and local perspective as well. A literature review on innovation and SME innovation strategies to their correlation and the possibility of their joint examination. Purpose of the article: The aim of this paper is to explore the SME’s innovation strategies and their impact on effectiveness of innovation in a peripheral region. We investigate the effects of innovation activities not only among small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…This shows the importance of enterprises from the SME sector for economic growth. Due to the extremely high importance of small and medium-sized enterprises in the economy, issues related to risk management in this type of enterprises are even more important (Kot et al, 2018;Pisar & Bilkova, 2019;Lewandowska & Stopa, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This shows the importance of enterprises from the SME sector for economic growth. Due to the extremely high importance of small and medium-sized enterprises in the economy, issues related to risk management in this type of enterprises are even more important (Kot et al, 2018;Pisar & Bilkova, 2019;Lewandowska & Stopa, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among them, the most number of, the backbone of the economy, fulfilling the needs within the nation as well as of bigger industries are small and medium enterprises. Small and medium enterprises have a key role in the economic acceleration of any nation and it plays a crucial role in employment generation, promoting innovation, competitiveness and economic growth (Kozubíková, Homolka, & Kristalas, 2017;Noorali & Gilaninia, 2017;Lewandowska & Stopa, 2019). And there is a direct link between the emergence of entrepreneurship and small and medium enterprise's growth and development (Gosevska, Popovski, & Markoski, 2013;Dvorský et al, 2019) and for the SMEs development and growth, the most vital ingredient is favorable business environment (Buno, Nadanyiova, & Hraskova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that—depending on specific conditions—all these feedbacks can be both positive and negative, and their effects overlap, which creates a complex pattern of industrial processing in Poland. The innovative activity of enterprises also depends on many other factors such as the national and international environment [ 14 , 15 , 16 ], management system [ 17 ], business support organizations [ 18 , 19 ], intellectual assets [ 20 ], sectoral patterns of cooperation and technology level [ 21 ], for which the ceteris paribus assumption was made. It can also affect other economic variables such as total factor productivity [ 22 ], the level of firm productivity [ 23 ], and anti-crisis reputational sustainability [ 24 ].…”
Section: Introductionmentioning
confidence: 99%